(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
This extensive study examines the effectiveness of the medicinal herbs Heracleum rigens,Eryngium foetidum L., and Passiflora subpeltata against various microorganisms. The alarming rise inantimicrobial resistance has prompted scientists to look for healing compounds in nature. There is a longhistory of traditional usage for these plants, and they have also been studied for their possibleantibacterial qualities.